1997
DOI: 10.1093/glycob/7.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of glycosphingolipids in human atherosclerotic plaque and unaffected aorta tissues

Abstract: We have measured the levels of glycosphingolipids and the activity of glycosphingolipid glycosyltransferases in human aortic intima and media from patients who died of atherosclerosis. The effects of lactosylceramide (LacCer) and glucosylceramide (GlcCer) from plaque intima on smooth muscle cell proliferation were assessed. When the GlcCer data was expressed as (micrograms GlcCer/mg cholesterol and/mg total phospholipid, a 28-fold and 7-fold increase in plaque intima compared to normal intima was observed. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 21 publications
3
58
0
2
Order By: Relevance
“…48,49 More recently, it was reported that there is marked accumulation of glucosylceramide and lactosylceramide in human atherosclerotic plaques. 50,51 The activity of SPT, the rate-limiting enzyme in sphingolipid synthesis, is also increased in rabbit aorta during experimental atherogenesis. 52 Taken together, these findings support the concept that enhanced sphingolipid synthesis leading to the enrichment of lipoproteins with ceramide, glucosylceramide, and sphingomyelin may be an important determinant of their atherogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 More recently, it was reported that there is marked accumulation of glucosylceramide and lactosylceramide in human atherosclerotic plaques. 50,51 The activity of SPT, the rate-limiting enzyme in sphingolipid synthesis, is also increased in rabbit aorta during experimental atherogenesis. 52 Taken together, these findings support the concept that enhanced sphingolipid synthesis leading to the enrichment of lipoproteins with ceramide, glucosylceramide, and sphingomyelin may be an important determinant of their atherogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…11 Increased activity of GalT-2 and increased levels of LacCer in familial hypercholesterolemia and in atherosclerosis has been reported. 12,13 The levels of other GSLs in fatty streaks and plaques have also been reported. 13,14 Nevertheless, up to now, a human metabolic disease due to the abnormal biosynthesis of GSL has not been shown.…”
Section: Sphingolipids: Structure Biosynthesis Degradation and Locmentioning
confidence: 97%
“…12,13 The levels of other GSLs in fatty streaks and plaques have also been reported. 13,14 Nevertheless, up to now, a human metabolic disease due to the abnormal biosynthesis of GSL has not been shown. In fact, the biochemical basis of several inherited sphingoglycolipidoses is due to the inability of these patients to hydrolyze various GSLs and sphingomyelin.…”
Section: Sphingolipids: Structure Biosynthesis Degradation and Locmentioning
confidence: 97%
“…DISCUSSION A number of reports have appeared on the modulation of cell growth and differentiation by glycosphingolipids (23-25). In the past few years, several groups have reported an accumulation of gangliosides in atherosclerosis vessels (35,36). Many of these studies were performed by adding exogenous glycolipids into the culture medium of cell lines under investigation.…”
Section: Fig 7 Effect Of Gd3 Synthase Gene On Tnf-␣-induced Mmp-9 Ementioning
confidence: 99%
“…On the other hand, the overexpression of GD3 synthase led to apoptosis in human leukemic cells (34). In the past few years, increased levels of GD3 have been found to be associated with proliferative disease, such as atherosclerosis (35,36). A recent study suggested that exogenously supplied GD3 has a dual role in modulating VSMC proliferation and apoptosis (37).…”
mentioning
confidence: 99%